Hak dan Kedudukan Harta Waris bagi Anak Angkat (Studi Kasus No. 71/PDT.G/2011/PN.PL.R) - Diva Darda Davita; Dewi Astutty Mochtar (Bhirawa Law Journal, 2022)
The purpose of marriage according to Article 1 of Law Number 1 of 1974 is to createa happy family and to have children. However, there are some married couples whoare not blessed with children due to several factors. This is the background of theresearch entitled Rights and Status of Inheritance for Adopted Children. The problemis discussing how the rights and position of inheritance for adopted children and howthe distribution of inheritance for adopted children. The method used is normativejuridical, namely research that is produced from library materials that have beenstudied, both sources obtained from books, journals, laws and regulations concernedwith the discussion of the issues raised. The results of this study are that adoptedchildren have the same rights and position as legitimate children in certain matters,but in terms of inheritance, adopted children have 1/3 rights in the form of grants. Inaddition to grants, adopted children can get assets left by the heir, if the heir has made a will before he dies.